Bioremediasi Lahan Tercemar Pestisida dengan Cara Pengomposan di Perkebunan Apel Batu - Yayok Suryo Purnomo; Gusvia Kusuma Dhiningrum (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
The use of unprocedural and ineffective intensive synthetic pesticides by farmers in Batu City has become commonplace and is common. An alternative treatment that can be done is to utilize the activity of microorganisms to degrade these pesticides, which is called bioremediation. Preliminary research was conducted to determine the quality of pesticide-contaminated soil by varying the C/N ratio and water content. The main research was carried out by calculating pesticide residues in the soil using the shaker method and then injecting them into Gas Chromatography-Mass Spectrometry (GC-MS). To determine the activity of microorganisms, we isolated microorganisms. The composting temperature is close to room temperature on days 25–28. The decrease in temperature causes the activity of bacteria to decrease. The C/N 30 treatment showed the lowest residue concentration compared to the C/N ratios of 35 and 40. The C/N 30 treatment consisted of soil, cow dung, organic matter residue, and sawdust. The reduction in pesticide residues (99%) was higher than the control and treatment, with a C/N ratio of 40. The variation in the C/N ratio in the bioremediation process affected the rate of degradation of the pesticide. Pesticide residues in the control, C/N 40, C/N 35, and C/N 30, respectively, decreased in concentration during the 28 days of the composting process as follows: 48.3%, 86.2%, 89.7%, and 99.3%. Based on these results, it can be concluded that the C/N 30 treatment had the highest pesticide degradation rate. The results of testing the growth of the population or colony of microorganisms showed that the increase in the number of colonies of microorganisms and the activity of microorganisms was followed by a decrease in pesticide residues. The reduction in pesticide residues at C/N 30 was 98%; this result showed a higher value compared to the control, C/N 40, and C/N 35.